A CLINICAL STUDY ON AMLAPITTA AND ITS MANAGEMENT WITH CHHINNODBHAVADI GHANAVATI - Nibedita, Mohapatra; Debasis, Biswal; Seema Krishna, Murthy; Vishnu Dutt, Sharma; Siddaram, *Arawatti (International Journal of Ayurveda and Pharma Research, 2016)
Amlapitta is a disease prevalent all over the world. The increasing prevalence rate is a constant challenge to the research workers. The disease Amlapitta is a common functional disease of Annavaha srotas. Materialistic life style provokes people to run behind a busy, stressful life with least concern towards proper food habit. The aim of the present study was to find out efficacy of Chhinnodbhavadi Ghanavati in comparison to modern PPI. In present study total 40 patients were taken, divided into 2 equal groups. In group-I: 20 patients were treated with oral administration of trial drug that is Chhinnodbhavadi ghanavati 500mg 2 tab twice a day for 45 days and in group-II: 20 patients were treated with control drug that is Pantaprazole 40mg 1 tab once a day orally for 45 days. After conducting clinical trial on 40 patients, observation and results were obtained. Statistical analysis shows that both trail and control drug were significantly effective to reduce the cardinal symptoms. As compared to trail drug the effect of control drug is better to reduce symptoms. However as compared to side effects and contra-indications of the control drug, it is advisable to use Chhinnodbhavadi Ghanavati for the treatment of Amlapitta for a long period.